Effects of arbuscular mycorrhizal fungus inoculation on the growth and nitrogen metabolism of Catalpa bungei C.A.Mey. under different nitrogen levels - Chen, Wei; Mou, Xueli; Meng, Panpan; Chen, Juan; Tang, Xiaan; Meng, Guihua; Xin, Kexu; Zhang, Yi; Wang, Chunyan (Frontiers in Plant Science, 2023)
Evidence suggests that arbuscular mycorrhizal fungi (AMF) may promote the growth of woody plants. However, the effects of AMF on nitrogen (N) metabolism in plants, especially trees, and its regulatory mechanism are rarely reported. Here, the effects of AMF inoculation on the growth and N nutrition status of Catalpa bungei under different N levels were reported. Three N levels (low, medium, high) and two mycorrhizal inoculation treatments (inoculation with Rhizophagus intraradices or not) were used with factorial design. The results showed that medium N could significantly improve the physiological metabolism and growth of C. bungei seedlings. However, when N was excessive, growth was significantly inhibited whether inoculated AMF or not. Compared with non-inoculated treatments, AMF inoculation could promote the absorption of N and P, improve photosynthesis under low to medium N levels, thus promoting the growth of seedlings. AMF changed the biomass allocation in seedlings by reducing the stem mass ratio and root/shoot ratio, and increasing the leaf mass ratio. At medium N levels, compared with non-inoculated treatment, AMF inoculation could significantly promote root growth by changing root hormone levels and improving root architecture and root activity. Under N addition, AMF inoculation could improve the absorption and assimilation of N by regulating the expression of key enzyme genes of N metabolism and nitrate transporter genes (NRT2.4, NRT2.5, NRT2.7) in roots, and enhancing the activities of the key enzyme of N metabolism. This study may provide a reference for the application of AMF in the cultivation and afforestation technology of C. bungei in Northwest China.